2009
DOI: 10.1155/2009/341268
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Treatment of Anterior Vaginal Wall Prolapse and Stress Urinary Incontinence with Transobturator Tension-Free Vaginal Mesh (Prolift) and Concomitant Tension-Free Vaginal Tape-Obturator

Abstract: Objective. It is to assess the feasibility, effectiveness, and safety of transobturator tension-free vaginal mesh (Prolift) and concomitant tension-free vaginal tape-obturator (TVT-O) system as a treatment of female anterior vaginal wall prolapse associated with stress urinary incontinence (SUI). Patients and Methods. Between December 2006 and July 2007, 20 patients with anterior genital prolapse and voiding dysfunction were treated with the transobturator tension-free vaginal mesh (Prolift) and concomitant te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…Furthermore, no bladder injury was observed in two groups, which was consistent with the previous report [23], indicating that the modified procedure was not inferior to Prolift-a in terms of safety. However, three other literatures reported 1.2, 3.5, and 4.3% incidence of bladder injuries during the anterior procedure, respectively [2,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, no bladder injury was observed in two groups, which was consistent with the previous report [23], indicating that the modified procedure was not inferior to Prolift-a in terms of safety. However, three other literatures reported 1.2, 3.5, and 4.3% incidence of bladder injuries during the anterior procedure, respectively [2,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…As many as 80% of urinary incontinent women have coexisting pelvic organ prolapse (POP). Among them, anterior vaginal wall prolapse is common and treatment becomes indicated as symptomatic prolapse develops.…”
Section: Introductionmentioning
confidence: 99%
“…Abou-Elela et al [13] reported the results of Prolift TM and TVT-O in 20 patients. In that study, the patients were all cured with no complications.…”
Section: Discussionmentioning
confidence: 99%